A case report of tracheal inflammatory myofibroblastic tumor in a 34-week pregnant woman misdiagnosed with asthma. Issue 33 (August 2017) - Li, Xiaochen; Li, Juan; Rao, Xiaoling; Ao, Qilin; Cao, Xiaopei; Huang, Yali; Zhang, Shengding; Fang, Xiaoyu; Liu, Xiansheng; Xie, Min
Abstract: Rationale: Inflammatory myofibroblastic tumor (IMT) is an uncommon neoplastic entity with a tendency of local recurrence and a low risk of distant metastasis. Involvement of trachea is extremely rare. Patient concerns: A 34-week pregnant woman previously diagnosed with asthma for 2 months was admitted with persistent wheezing and hemoptysis. A computed tomography scan and bronchoscopy revealed a gigantic polyp in the trachea. Diagnoses: Tracheal inflammatory myofibroblastic tumor. Interventions: The mass was removed with an electrocautery snare and identified histologically as an IMT. Further immunochemical staining showed strong positive staining for smooth muscle actin and platelet-derived growth factor receptor α (PDGFRA), weak positive staining for caldesmon, and negative staining for anaplastic lymphoma kinase (ALK)1, desmin, S-100, and CD34. The tracheal IMT strongly expressed estrogen receptor-α (ER-α), which indicated that the development of this rare IMT might have been associated with hormone fluctuations that occurred during the pregnancy. Outcomes: Follow-up and histological analyses revealed no evidence of recurrence and metastasis. Lessons: This report describes an extremely rare case of a tracheal IMT that presented a diagnostic dilemma for the clinician and the pathologist. Tracheal IMT is a challenge for the clinician in diagnosis due to the nonspecific clinical presentation. Histology and immunohistochemistry are required to reach an accurate diagnosis of IMT.